Yield and Zinc Concentration of Several Rice Plant Varieties (Oryza Sativa L.) With Zinc Sulfate Heptahydrate (ZnSO4) Fertilization - Priyanto, Yuda Galang; Purwanto, Edi; Rahayu, Muji (Agro Bali : Agricultural Journal, 2024)
Zinc is an essential micronutrient for the survival of plants. Rice cultivation in Indonesia is primarily conducted on submerged soil, resulting in low zinc availability in rice plants. Applying zinc fertilizer is a method to augment plant nutrients, consequently enhancing rice yield. This study aimed to analyze and determine the best ZnSO4 fertilization dose for yield and zinc concentration in Ciherang, Rojolele and Mentik Wangi rice varieties. This study was conducted in the experimental garden of Sebelas Maret University from August 2023 to January 2024. The study was conducted using a 3x5 factorial Randomized Complete Block Design. The first factor was rice varieties consisting of Ciherang, Rojolele, and Mentik Wangi. The second factor was ZnSO4 fertilization consisting of doses of 0 kg.ha-1, 12 kg.ha-1, 16 kg.ha-1, 20 kg.ha-1, and 24 kg.ha-1. Statistical analysis in this study used ANOVA with a significance level of 5% and DMRT with a significance level of 5%. Zinc sulfate heptahydrate (ZnSO4) foliar application significantly differs in rice's zinc concentration. Mentik wangi rice variety (V3) was given dose 4 (D4) (24 kg.ha-1) is the best combination to increase the zinc concentration in rice by 40.01 ppm compared to no zinc fertilization treatment.